PERUBAHAN SISTEM PASAR LADA PUTIH DI KEPULAUAN BANGKA BELITUNG - David Oktaviandi; Hamdan . (JEM Jurnal Ekonomi dan Manajemen, 2017)
Indonesia has been known as one of the main pepper producing countries known in the world market, white pepper is species known as Muntok White Pepper which is mainly produced by Bangka-Belitung Province and Black Pepper known as Lampung Black Pepper produced by Lampung Province.. The decrease of pepper production in Bangka Belitung can be identified also by the decreasing of land area for pepper cultivation because there are other sectors such as tin mining sector. The condition of land conversion and the transfer of farming profession to mining is caused by many factors involved, one of which is the market system. The method used in this research is quantitative and descriptive qualitative method which gives an idea how the change of white pepper market system in Bangka Belitung Islands. The results show that there are two events that affect the pepper market system, first; the green revolution made through the policy of subsidizing an organic fertilizer in improving productivity but having an impact on the emergence of problems such as soil acidity increase which causes the emergence of pest attacks are often encountered in pepper cultivation currently. Second; after the existence of regional autonomy policy which indirectly affect pepper commodity by giving incentive to mining sector and indirectly happened disincentive to commodity of pepper